Research on factors affecting customer satisfaction with deposit and loan services at Vietnam Export-Import Commercial Joint Stock Bank - An Giang Branch - Khuong Thi, Hue (Technium Social Sciences Journal, 2025)
Global economic integration has significantly impacted Vietnam’s banking sector, increasing competition with foreign banks. This competitive environment emphasizes the importance of customer satisfaction as a key factor for banks to thrive. This study investigates customer satisfaction with deposit and loan services at the Vietnam Import-Export Commercial Joint Stock Bank, An Giang Branch (Eximbank-An Giang). Using a modified SERVPERF model, the study evaluates how service quality dimensions—reliability, responsiveness, assurance, empathy, tangibles, and price competitiveness—affect customer satisfaction. The research process included preliminary qualitative research to adapt the SERVPERF scale and formal quantitative research using surveys. A sample size of 222 valid responses was analyzed using exploratory factor analysis and multiple regression. Results indicate that customer satisfaction is positively influenced by responsiveness, tangibles, assurance, empathy, and price competitiveness, with responsiveness having the strongest impact. Variance analysis revealed significant differences in satisfaction levels based on service type, occupation, income, distance to transaction locations, and education level. However, no differences were observed across gender, age, transaction duration, or frequency. Findings provide Eximbank-An Giang with actionable insights to enhance service quality and competitiveness. Despite its contributions, the study is limited by non-probability sampling and its focus on deposit and loan services, which may restrict the generalizability of results. Future research should expand the geographical scope and explore satisfaction with other banking services. This study serves as a foundation for developing targeted policies to improve customer satisfaction, fostering loyalty and competitiveness in the dynamic banking market.